ANALISIS INVESTASI ASET, STRUKTUR KEPEMILIKAN, ARUS KAS OPERASI, STRUKTUR MODAL TERHADAP PERTUMBUHAN PERUSAHAAN DENGAN GCG (GOOD CORPORATE GOVERNANCE) SEBAGAI INTERVENING PADA PERUSAHAAN TEXTILE & GARMENT YANG TERDAFTAR DI BEI TAHUN 2021–2024 - Jeselin Devi Adesya Felandy; Hwihanus Hwihanus (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of asset investment, ownership structure, operating cash flow, and capital structure on firm growth, with Good Corporate Governance (GCG) as an intervening variable in textile and garment companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research employs a quantitative approach using Partial Least Square–Structural Equation Modeling (PLS-SEM). The findings show that asset investment has no significant effect on firm growth but has a significant negative effect on operating cash flow. Ownership structure does not significantly affect either operating cash flow or firm growth. Capital structure has a significant negative effect on operating cash flow, yet it does not significantly influence firm growth. Operating cash flow also shows no significant effect on firm growth. Furthermore, GCG does not strengthen the relationship between operating cash flow and firm growth. Overall, the study concludes that most internal factors have not been able to serve as the main drivers of firm growth within the textile industry during 2021–2024 due to high cost pressures, market instability, and substantial financial burdens